Transfer pricing for financial institutions - Smullen, John (Woodhead Pub., 2001)
A cutting-edge study of transfer pricing in the increasingly competitive financial services sector. It examines the many issues involved and suggests different techniques for establishing efficient transfer pricing systems. This book is essential reading for all organisations that raise and loan funds in today's global markets.